Vortex dynamics in NbTi films at high frequency and high DC magnetic fields - Gianluca Ghigo; Daniele Torsello; Laura Gozzelino; Michela Fracasso; Mattia Bartoli; Cristian Pira; Davide Ford; Giovanni Marconato; Matteo Fretto; Ivan De Carlo; Nicola Pompeo; Enrico Silva (Scientific Reports, 2023)
Abstract We report on the characterization of NbTi films at $$\sim$$ ∼ 11 GHz and in DC magnetic fields up to 4 T, performed by means of the coplanar waveguide resonator technique, providing quantitative information about the penetration depth, the complex impedance, and the vortex-motion-induced complex resistivity. This kind of characterization is essential for the development of radiofrequency cavity technology. To access the vortex-pinning parameters, the complex impedance was analyzed within the formalism of the Campbell penetration depth. Measurements in this frequency range allowed us to determine the complete set of vortex-pinning parameters and the flux flow resistivity, both analyzed and discussed in the framework of high-frequency vortex dynamics models. The analysis also benefits from the comparison with results obtained by a dielectric-loaded resonator technique on similar samples and by other ancillary structural and electromagnetic characterization techniques that provide us with a comprehensive picture of the material. It turns out that the normalized flux flow resistivity follows remarkably well the trend predicted by the time dependent Ginzburg-Landau theory, while the pinning constant exhibits a decreasing trend with the field which points to a collective pinning regime.